IMPLIKASI KEBIJAKAN PEMBLOKIRAN APLIKASI TIKTOK OLEH AMERIKA SERIKAT TERHADAP HUBUNGAN TIONGKOK DAN AMERIKA SERIKAT DISEKTOR KEAMANAN RUANG SIBER: BYTEDANCE, TIONGKOK - Wyanne Teresita Saputra (2021)
Digitalization is a familiar thing in all parts of the world, which are also affected by the era of globalization. Technological developments follow the times where today, everything is sophisticated and efficient. The TikTok application is here as proof of the current digital era which is very pleasing to the international community and can even be downloaded by millions of users. One of the users with the largest downloads is the United States of America. However, the TikTok application was allegedly taken and used to exploit user data for other purposes, until the United States decided a policy to block the application from its national security interests. The purpose of this study is to explain how to find out if the TikTok application is blocked on the relationship between the United States and China using the theory of national interest and cyber security with the concept of cyber. Using a qualitative research approach with the type of exploratory research. The results show that the policy of blocking the TikTok application can exacerbate the cyber war that has occurred before in the relations between the United States and China on the security of their cyberspace.